Introduction English Literacy through Vocabulary Memorization in Students - Vegi Mutiarah; Dian Riani Said; Achmad Dahlan Abdullah (Jurnal Pendidikan Indonesia, 2025)
Indonesia, with a population of 278,696,200 as of July 4, 2023, is ranked as the fourth most populous country in the world. Lacking official school permits and high education fees, they often continue their education at guidance centers, such as the one in Subang Mewah, Selangor. One of the main problems faced is the low achievement of literacy among elementary school students, especially in memorization skills. The lack of emphasis on teaching vocabulary hinders the development of students' English language skills. This research aims to improve students' literacy skills in English by implementing environment-based vocabulary learning methods that are relevant to students, in order to improve their understanding of the English language. This study uses a qualitative approach with a vocabulary teaching method that connects words with everyday objects, such as household items and objects in the classroom. Data were collected through direct observation and interviews with students regarding their interests and engagement in learning. After the application of the method, students show increased enthusiasm in learning English vocabulary. They are more interested in mastering the basics of English and show a greater curiosity about the language. Learning vocabulary that connects to students' environments is effective in improving their literacy in speaking and listening. This method not only improves language skills but also arouses students' interest in English. This research can be a reference for educators and education policy in developing innovative literacy strategies, especially in the context of education abroad for Indonesian students studying abroad, such as in Malaysia. The application of context-based methods can improve the overall quality of English language learning.